2006
DOI: 10.1136/jcp.2005.034702
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide in reversible myocardial ischaemia: Table 1

Abstract: Background: Coronary heart disease is associated with increased B-type natriuretic peptides (BNPs), and, although controversial, may cause exaggerated exercise-induced BNP secretion. We investigated BNP in relation to reversible myocardial ischaemia. Materials and methods: Serum N-terminal proBNP (NTproBNP) was measured before and after an exercise electrocardiogram test (ETT) in 14 patients with and 45 patients without exercise-induced myocardial ischaemia. Statistical analysis was carried out on logarithmica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…also reported similar results 32,33. On the other hand, other studies reported contradictory findings 34,35. In a study, before and after exercise testing, serum NT-proBNP levels were studied hourly for six hours and NT-proBNP levels were not found to be correlated with myocardial ischaemia 36…”
Section: Discussionmentioning
confidence: 64%
“…also reported similar results 32,33. On the other hand, other studies reported contradictory findings 34,35. In a study, before and after exercise testing, serum NT-proBNP levels were studied hourly for six hours and NT-proBNP levels were not found to be correlated with myocardial ischaemia 36…”
Section: Discussionmentioning
confidence: 64%
“…Wang et al [8] also observed a strong association between atrial fibrillation and NT-proBNP. As to the effect of myocardial ischemia, our findings are difficult to compare with other studies, because dyspnea rather than angina or a positive exercise test was the criterion for entry [27]. The response of NT-proBNP secretion to ischemic episodes causing dyspnea may differ from the response to ischemia presenting as angina pectoris [28].…”
Section: Discussionmentioning
confidence: 91%
“…in patients with the acute coronary syndrome, NT-proBNP is also found elevated and correlated to the concentrations of cardiac troponins [15,16]. It has been shown that myocardial ischaemia augments synthesis and release of natriuretic peptides and that hypoxia upregulates the BNPgene [17][18][19][20]. In the PEACE study on patients with low-risk stable coronary disease it was concluded that BNPs provide strong and incremental prognostic information to traditional risk factors [21].…”
Section: Discussionmentioning
confidence: 99%